2016
DOI: 10.12732/ijpam.v106i2.10
|View full text |Cite
|
Sign up to set email alerts
|

$1$-Movable Clique Dominating Sets of a Graph

Abstract: A clique (convex) dominating set S of G is a 1-movable clique dominating set (resp. 1-movable convex dominating set) of G if for every v ∈ S, either S \ {v} is a clique (resp. convex) dominating set or there exists a vertex u ∈ (V (G) \ S) ∩ NG(v) such that (S \ {v}) ∪ {u} is a clique (resp. convex) dominating set of G. The minimum cardinality of a 1-movable clique (resp. 1-movable convex) dominating set of G, denoted by γ 1 mcl (G) (resp. γ 1 mcon (G)), is called the 1-movable clique domination number (resp. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Other studies on domination are in [11], [12], [17], and [22]. Some studies involving cliques can be found in [5], [6], [7], [8], [13], [15], [18], and [23].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies on domination are in [11], [12], [17], and [22]. Some studies involving cliques can be found in [5], [6], [7], [8], [13], [15], [18], and [23].…”
Section: Introductionmentioning
confidence: 99%